2019
DOI: 10.1128/jvi.02174-18
|View full text |Cite
|
Sign up to set email alerts
|

Human Norovirus Neutralized by a Monoclonal Antibody Targeting the Histo-Blood Group Antigen Pocket

Abstract: Temporal changes in the GII.4 human norovirus capsid sequences occasionally result in the emergence of genetic variants capable of causing new epidemics. The persistence of GII.4 is believed to be associated with the recognition of numerous histo-blood group antigen (HBGA) types and antigenic drift. We found that one of the earliest known GII.4 isolates (in 1974) and a more recent epidemic GII.4 variant (in 2012) had varied norovirus-specific monoclonal antibody (MAb) reactivities but similar HBGA binding prof… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 42 publications
4
47
0
Order By: Relevance
“…The recently developed HuNoV culture system IECs derived from intestinal organoids (23), while experimentally challenging, has been used in a number of subsequent studies to examine the impact of disinfectants (52) and of monoclonal antibodies (53,54). This study set out to use an organoid-based system to assess the cellular pathways that restrict HuNoV replication and to further refine the experimental conditions that allow optimal growth of HuNoV in culture.…”
Section: Discussionmentioning
confidence: 99%
“…The recently developed HuNoV culture system IECs derived from intestinal organoids (23), while experimentally challenging, has been used in a number of subsequent studies to examine the impact of disinfectants (52) and of monoclonal antibodies (53,54). This study set out to use an organoid-based system to assess the cellular pathways that restrict HuNoV replication and to further refine the experimental conditions that allow optimal growth of HuNoV in culture.…”
Section: Discussionmentioning
confidence: 99%
“…From the first recognition in 1968 that a virus caused an outbreak of HuNoV gastroenteritis in an elementary school in Norwalk, Ohio (1), until 2016, there was no in vitro culture system of HuNoV in intestinal epithelial cells. A novel HuNoV culture system using human intestinal enteroids (HIEs) generated from stem cells isolated from human small intestinal crypts is now available and is being used worldwide to study virus replication, inactivation, and neutralizing antibodies (2)(3)(4)(5)(6)(7)(8)(9).…”
mentioning
confidence: 99%
“…The emergence of these variants has been correlated with changes on five different variable antigenic sites (namely, sites A to E) that map on the surface of the P domain; thus, new viruses can evade the human immune responses elicited to previously circulating variants (11,(18)(19)(20). Using the recently developed cell culture system for human noroviruses (21), two of these sites have been confirmed to be involved in virus neutralization (22). Studies have shown that antibodies that map to these sites can block the interaction of VP1 with carbohydrates from the HBGA; however, the antigenic sites of several monoclonal antibodies (MAbs) with blocking activity, raised against GII.4 viruses, have not been determined (11,12,19,(23)(24)(25).…”
mentioning
confidence: 99%